Osmo-, thermo- and ethanol- tolerances of Saccharomyces cerevisiae S1 - Balakumar,Sandrasegarampillai (2012)
Saccharomyces cerevisiae S1, which is a locally isolated and improved strain showed viability at 40, 45 and 50ºC and produced ethanol at 40, 43 and 45ºC. When the cells were given heat shock at 45ºC for 30min and grown at 40ºC, 100% viability was observed for 60h, and addition of 200gl-1 ethanol has led to complete cell death at 30h. Heat shock given at 45ºC (for 30min) has improved the tolerance to temperature induced ethanol shock leading to 37% viability at 30h. when the cells were subjected to ethanol (200gl-1 for 30 min) and osmotic shock (sorbitol 300gl-1), trehalose contents in the cells were increased. The heat shocked cells showed better viability in presence of added ethanol. Soy flour supplementation has improved the viability of S. cerevisiae S1 to 80% in presence of 100gl-1 added ethanol and to 60% in presence of 300gl-1 sorbitol. In presence of sorbitol (200gl-1) and ethanol (50gl-1) at 40ºC, 46% viability was retained by S. cerevisiae S1 at 48h and it was improved to 80% by soy flour supplementation.